INFLUENCE ,INVESTMENT AND GDP TO LEVEL OPEN UNEMPLOYMENT IN INDONESIA THE EFFECT OF INVESTMENT AND GDP ON THE OPEN UNEMPLOYMENT RATE IN INDONESIA . - Saharuddin; Muhammad Ali; Rico Nur Ilham; Frengki Putra Ramansyah (RADJA PUBLIKA, 2026)
Study This aim For can know investment impact And Product Domestic Gross Domestic Product (GDP) on the unemployment rate in Indonesia. Data analysis methods used in this study This is data quantitative in the form of data secondary with model ARDL withThe total number of observations is 44, with the number of years being 1980 – 2024. The results of the short-term research show that investment and Gross Domestic Product have a positive and negative effect. on the unemployment rate in Indonesia. Then in the long term, investment and Gross Domestic Product have a positive and significant impact on the open unemployment rate in Indonesia.